Acceleration of Evaluation, Synthesis and Selection of Engineering Solutions by Morphological Approaches - Rakov Dmitry (EDP Sciences, 2021)
The article discussed the issues of creating a decision support system in the design process. It is based on morphological methods and approaches. These approaches can be successfully used to accelerate the evaluation, synthesis and selection of engineering solutions at the conceptual design stage. With the help of combinatorics, it is possible to generate a significant number of different engineering solutions. The conceptual stage is the most important in determining the future parameters and characteristics of the designed systems. The article also considers the possibility of computerization of the morphological approach. All this leads to an increase in the efficiency of the design process as a whole.